Our 5-Year Clinical Experience in Idiopathic Sudden Sensorineural Hearing Loss - Aksoy, Ahmet; Özata Güngör, Özge (ENT Updates, 2023)
Background: The aim of the study was to determine which steroids effectively treat idiopathic sudden sensorineural hearing loss (ISSNHL). Methods: Records of patients who were followed up for ISSNHL diagnosis between 2014 and 2018 were retrospectively analyzed. The efficacy of different steroids (systemic, intratympanic, and systemic+intratympanic) in the treatment of ISSNHL was evaluated. Eighty-nine patients diagnosed with ISSNHL were included in the study. In addition to steroid treatment, all groups received standard treatment. It was observed that 43 patients received steroid treatment orally, 17 received intratympanic, and the remaining 23 received combination treatment. The recovery was evaluated according to the modified Siegel’s criteria. Results: The mean age of the patients was 50.2 ± 14.7 years; 60% (n=53) were male, and 40% (n=36) were female. The median values of pure tone averages before treatment were 43.41 ± 17.92 dB, 53.9 ± 14.70 dB, and 51.86 ± 12.76 dB in the systemic steroid, intratympanic steroid, and combined treatment groups, respectively. After treatment, hearing levels improved by 22.62 ± 15.87 dB, 38.4 ± 18.83 dB, and 34.26 ± 17.98 dB, respectively. The treatment efficacy of the groups was statistically significant in terms of pure tone averages (P < .05). The improvement rate with systemic treatment was 4.25 times higher than that of intratympanic treatment. There was no significant difference between patients who received intratympanic treatment and those who received combination therapy (P=.55). There was no significant difference between patients receiving systemic and combination treatments (P=.058). Conclusion: Systemic steroids are more effective than intratympanic treatment for ISSNHL. This study showed that systemic steroids were more effective during initial treatment.